Managing change at work desktop learning for busy professionals (Menlo Park, Calif. : Crisp Learning, 2001)
This self-directed learning package contain information how to communicate effectively about change, manage transitions and internal cultural change and how to create positive results
System requirements : Windows 95 or later or Windows NT 4 or later ; Pentium (90MHz or faster) ; 3 MB fess ; 16 MB memory(RAM) ; 2x or faster CD-ROM; 800 x 600 monitor resolution; browser software such as Internet Explorer or Netscape Navigator.
Keywords: Organizational change -- Management